2020
DOI: 10.1002/ijc.33387
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting morbidity profile of women newly diagnosed with breast cancer in sub‐Saharan Africa: African Breast Cancer—Disparities in Outcomes study

Abstract: The presence of preexisting morbidities poses a challenge to cancer patient care. There is little information on the profile and prevalence of multi‐morbidities in breast cancer patients across middle income countries (MIC) to lower income countries (LIC) in sub‐Saharan Africa (SSA). The African Breast Cancer–Disparities in Outcomes (ABC‐DO) breast cancer cohort spans upper MICs South Africa and Namibia, lower MICs Zambia and Nigeria and LIC Uganda. At cancer diagnosis, seven morbidities were assessed: obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…In our previous studies, we found that women who were obese and hypertensive were more likely to present with early-stage breast cancer and that multimorbidity was not associated with the stage of breast cancer diagnosis [ 12 , 16 ]. We also found that in early-stage breast cancer, women with multimorbidity were less likely to have surgery, less likely to receive chemotherapy, and more likely to receive endocrine therapy than those with a low multimorbidity burden [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we found that women who were obese and hypertensive were more likely to present with early-stage breast cancer and that multimorbidity was not associated with the stage of breast cancer diagnosis [ 12 , 16 ]. We also found that in early-stage breast cancer, women with multimorbidity were less likely to have surgery, less likely to receive chemotherapy, and more likely to receive endocrine therapy than those with a low multimorbidity burden [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients, and especially those who are elderly, may have comorbidities when they are diagnosed with cancer. 6 Previous studies have shown that 20-35% of women with breast cancer have one or more comorbidities at the time of breast cancer diagnosis. 6 The presence of comorbidities at the time of diagnosis of breast cancer poses an additional challenge for the management of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…6 Previous studies have shown that 20-35% of women with breast cancer have one or more comorbidities at the time of breast cancer diagnosis. 6 The presence of comorbidities at the time of diagnosis of breast cancer poses an additional challenge for the management of the disease. 7 Communicable disease, urbanization, and cardiovascular disease are risk factors for breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations